Height and body mass index in molecularly confirmed Silver–Russell syndrome and the long‐term effects of growth hormone treatment. (21st March 2022) - Lokulo‐Sodipe, Oluwakemi; Giabicani, Eloïse; Canton, Ana P. M.; Ferrand, Nawfel; Child, Jenny; Wakeling, Emma L.; Binder, Gerhard; Netchine, Irène; Mackay, Deborah J. G.; Inskip, Hazel M.; Byrne, Christopher D.; Temple, I. Karen; et al.
Abstract: Objective: Silver–Russell syndrome (SRS) causes short stature. Growth hormone (GH) treatment aims to increase adult height. However, data are limited on the long‐term outcomes of GH in patients with molecularly confirmed SRS. This study evaluated height, body mass index (BMI) and GH treatment in molecularly confirmed SRS. Design: An observational study with retrospective data collection. Patients: Individuals with molecularly confirmed SRS aged ≥13 years. Measurements: Data were collected on height, height gain (change in height standard deviation score [SDS] from childhood to final or near‐final height), BMI and gain in BMI (from childhood to adulthood) and previous GH treatment. Results: Seventy‐one individuals (40 female) were included. The median age was 22.0 years (range 13.2–69.7). The molecular diagnoses: H19/IGF2:IG‐DMR LOM in 80.3% (57/71); upd(7)mat in 16.9% (12/71) and IGF2 mutation in 2.8% (2/71). GH treatment occurred in 77.5% (55/71). Total height gain was greater in GH‐treated individuals (median 1.53 SDS vs. 0.53 SDS, p = .007), who were shorter at treatment initiation (−3.46 SDS vs. −2.91 SDS, p = .04) but reached comparable heights to GH‐untreated individuals (−2.22 SDS vs. −2.74 SDS, p = .7). In GH‐treated individuals, BMI SDS was lower at the most recent assessment (median −1.10 vs. 1.66, p = .002) with lower BMI gain (2.01 vs. 3.58, p = .006) despite similar early BMI SDS to GH‐untreated individuals (median −2.65 vs. −2.78, p = .3). Conclusions: These results support the use of GH in SRS for increasing height SDS. GH treatment was associated with lower adult BMI which may reflect improved metabolic health even following discontinuation of therapy.